The Career Prospects of Overeducated Americans - Brian Clark; Clement Joubert; Arnaud Maurel (Institute for the Study of Labor (IZA), 2014)
In this paper we analyze career dynamics for the large share of U.S. workers who have more schooling than their peers in the same occupation. We use data from the NLSY79 combined with the CPS to analyze transitions into and out of overeducated employment, together with the corresponding effects on wages. Overeducation is a fairly persistent phenomenon at the aggregate and individual levels, with 66% of workers remaining overeducated after one year. Overeducation is not only more common, but also more persistent among blacks and low-AFQT individuals. Further, the hazard rate out of overeducation drops by about 60% during the first 5 years spent overeducated. However, the estimation of a mixed proportional hazard model suggests that this is attributable to selection on unobservables rather than true duration dependence. Finally, overeducation is associated with lower current as well as future wages, which points to the existence of scarring effects.
Keywords: J24; I21; 330; overeducation; mismatch